2020
DOI: 10.1177/0192513x20934834
|View full text |Cite
|
Sign up to set email alerts
|

A Dyadic Study on Perceived Stress and Couple Adjustment During Pregnancy: The Mediating Role of Depressive Symptoms

Abstract: Stress is associated with dyadic adjustment during transition to parenthood, but little is known about mechanisms underlying this link, particularly during prenatal period. This dyadic study explored the mediating role of depressive symptoms in the relationship between perceived stress and dyadic adjustment in expectant couples. One hundred and fourteen couples at the third trimester of pregnancy completed self-reports of perceived stress, depression, and dyadic adjustment. Results indicated that both parents’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 71 publications
(86 reference statements)
1
17
1
2
Order By: Relevance
“…Indeed, the cross‐sectional nature of the data prevents us from drawing conclusions about causal direction, even though the associations between variables in our study were invoked on a strong theoretical base because perceived stress during the past 6 months of pregnancy and poor marital satisfaction are thought to precede the risk of depressive states few weeks before the childbirth (Dayan et al., 2010). However, there have been dyadic studies that found that depression mediated the relation between stress and relationship satisfaction contrary to what we observed (Baldoni et al., 2020; Rollè et al., 2017). For this reason, future studies employing a longitudinal dyadic design should be conducted not only to identify the causal relationships among the variables, but also to clarify the impacts of perceived stress on marital satisfaction and levels of depressive symptoms over time (including several months after childbirth).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, the cross‐sectional nature of the data prevents us from drawing conclusions about causal direction, even though the associations between variables in our study were invoked on a strong theoretical base because perceived stress during the past 6 months of pregnancy and poor marital satisfaction are thought to precede the risk of depressive states few weeks before the childbirth (Dayan et al., 2010). However, there have been dyadic studies that found that depression mediated the relation between stress and relationship satisfaction contrary to what we observed (Baldoni et al., 2020; Rollè et al., 2017). For this reason, future studies employing a longitudinal dyadic design should be conducted not only to identify the causal relationships among the variables, but also to clarify the impacts of perceived stress on marital satisfaction and levels of depressive symptoms over time (including several months after childbirth).…”
Section: Discussioncontrasting
confidence: 99%
“…The third trimester of pregnancy is the final stretch of the prenatal period, and maternal health is considered the primary focus of the couple. Thus, maternal perceived stress may have an impact not only on her partner's marital satisfaction but also on her partner's affective states due to their link with a safe and successful childbirth (Baldoni et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the pandemic may be associated with relationship outcomes (Balzarini et al, 2020;Overall et al, 2020), given that health-related stress is linked to psychological distress and reduced life satisfaction (e.g., Meier et al, 2011), which can negatively impact relationship processes (e.g., Proulx et al, 2007;Manne et al, 2010;Rajaei et al, 2021). Further, perceived stress, a measure of global feelings of stress (Cohen et al, 1983), is likely to capture experiences of stress beyond just the domains of finances or health, including general stressors, which are consequential for relational well-being (Baldoni et al, 2020;Bodenmann, 1995). Taken together, various forms of stress are related to reduced relationship satisfaction (Archuleta et al, 2011;Barton et al, 2015;Karney et al, 2005), and they are associated with concerns about the long-term viability of the relationship through their harmful effects on relational interactions (Barton & Bryant, 2016;Conger et al, 1990;Gudmunson et al, 2007).…”
Section: Stress and Relationship Instabilitymentioning
confidence: 99%
“…Moreover, our results showed that psychologically distressed men reported higher perceived stress than the men at risk of externalized behavioral problems. According to previous studies, high perceived stress is associated to paternal affective disorders, especially with depressive and anxious symptomatology [ 3 , 26 , 27 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies identified significant associations between PPND and some individual variables such as high levels of perceived stress [ 16 , 17 ], multiparity [ 2 , 18 , 19 ], having a previous history of psychiatric disorders [ 20 ], and experiencing stressful life events (e.g., job loss, divorce, mourning) [ 21 , 22 ]. Other studies have highlighted the positive correlation between PPND and risk of perinatal depression in their partners [ 23 , 24 ] and the negative association between PPND and marital adjustment [ 11 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%